Penyelenggaraan Pembangunan NKRI Menuju Negara Maritim Berdasarkan Prinsip Negara Kepulauan - Aryono Putra; Yasser Arafat (JURNAL AKTA YUDISIA, 2021)
ABSTRACT Indonesia has been deprived of its own true roots as a maritime country. This is the success of the colonial Dutch colonialists who do "devide at empera" in which eventually the nation in the archipelago of this archipelago sees the sea as a separator and inhibitor space.The purpose of this novice lecturer's research is to Know the concept of archipelagic state and maritime state in Indonesia and to prove its implementation in policy and development direction in Indonesia. Is the Government Homeland use in marine activities as a prime mover and a pledge to increase the economy, (2) is supported by a fleet of strong civilian and military, and (3) contribute as much as possible for the prosperity of the people.The research method used in writing this beginner lecturers are socio-juridical legal research methods is often called legal sociological research based school of sociological jurisprudence. Judging from the effectiveness of law or facts that exist in the field which is then compared with the rules of positive law. Field data is used as important information in determining policy and regulatory arrangements and institutions in legal practice for island and coastal communities in Tarakan City, North Kalimantan Province.The results of this study that the Government of the Republic of Indonesia should re-arrange the grand design of a National System oriented to Indonesia as an archipelagic country and the State Archipelago. Keywords: islands, maritime, country, policy, kaltaraABSTRACT Indonesia has been deprived of its own true roots as a maritime country. This is the success of the colonial Dutch colonialists who do "devide at empera" in which eventually the nation in the archipelago of this archipelago sees the sea as a separator and inhibitor space.The purpose of this novice lecturer's research is to Know the concept of archipelagic state and maritime state in Indonesia and to prove its implementation in policy and development direction in Indonesia. Is the Government Homeland use in marine activities as a prime mover and a pledge to increase the economy, (2) is supported by a fleet of strong civilian and military, and (3) contribute as much as possible for the prosperity of the people.The research method used in writing this beginner lecturers are socio-juridical legal research methods is often called legal sociological research based school of sociological jurisprudence. Judging from the effectiveness of law or facts that exist in the field which is then compared with the rules of positive law. Field data is used as important information in determining policy and regulatory arrangements and institutions in legal practice for island and coastal communities in Tarakan City, North Kalimantan Province.The results of this study that the Government of the Republic of Indonesia should re-arrange the grand design of a National System oriented to Indonesia as an archipelagic country and the State Archipelago. Keywords: islands, maritime, country, policy, kaltara